Linguistic evolution - Ruhlen, Merritt (Henry Stewart Talks, 2007)
Discovery of comparative linguistics, The Indo-Hittite family, Fundamentals of linguistic taxonomy, Alfredo Trombetti, The Eurasiatic language family, African language families, The Dene-Caucasian family, The Amerind language family, Monogenesis, Origin and evolution of word order, Linguistic, genetic and archaeological evidence for human migrations
Archived at 2020/08/13